Question Number 208164 by Fridunatjan08 last updated on 06/Jun/24 | ||
![]() | ||
$${Solve}\:{for}\:{x}: \\ $$$${x}^{\mathrm{2}} +{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)+{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{\mathrm{2}} +{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{\mathrm{3}} +...+{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{\mathrm{100}} =\mathrm{1} \\ $$ | ||
Answered by A5T last updated on 06/Jun/24 | ||
![]() | ||
$${x}^{\mathrm{2}} +{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)+{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{\mathrm{2}} +...+{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{\mathrm{100}} =\mathrm{1} \\ $$$$\Rightarrow{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)+{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{\mathrm{2}} +...+{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{\mathrm{100}} =\mathrm{1}−{x}^{\mathrm{2}} \\ $$$${Dividing}\:{through}\:{by}\:\mathrm{1}−{x}^{\mathrm{2}} \:\left[{x}\neq\underset{−} {+}\mathrm{1}\right] \\ $$$$\Rightarrow{x}^{\mathrm{2}} +{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)+{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{\mathrm{2}} +...+{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{\mathrm{99}} =\mathrm{1} \\ $$$${Subtracting}\:\:{x}^{\mathrm{2}} \:{from}\:{both}\:{sides},\:{dividing}\:{by}\: \\ $$$$\left(\mathrm{1}−{x}^{\mathrm{2}} \right)\:{and}\:{iterating} \\ $$$$\Rightarrow{x}^{\mathrm{2}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right)=\mathrm{1}−{x}^{\mathrm{2}} \Rightarrow{x}^{\mathrm{2}} =\mathrm{1}\Rightarrow{x}=\underset{−} {+}\mathrm{1} \\ $$$${But}\:{by}\:{assumption}\:{that}\:{x}\neq\underset{−} {+}\mathrm{1}\:{initially} \\ $$$$\Rightarrow{x}=\underset{−} {+}\mathrm{1} \\ $$ | ||
Commented by Fridunatjan08 last updated on 07/Jun/24 | ||
![]() | ||
$${thanks}\:{sir}. \\ $$ | ||
Answered by Berbere last updated on 07/Jun/24 | ||
![]() | ||
$${x}^{\mathrm{2}} \left(\underset{{k}=\mathrm{0}} {\overset{\mathrm{100}} {\sum}}\left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{{k}} \right)=\mathrm{1}\Rightarrow{x}\neq\mathrm{0} \\ $$$${x}^{\mathrm{2}} .\frac{\mathrm{1}−\left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{\mathrm{101}} }{{x}^{\mathrm{2}} }=\mathrm{1} \\ $$$$\Leftrightarrow\mathrm{1}−\left(\mathrm{1}−{x}^{\mathrm{2}} \right)^{\mathrm{101}} =\mathrm{1}\Rightarrow{x}^{\mathrm{2}} =\mathrm{1}\Rightarrow{x}\in\left\{−\mathrm{1},\mathrm{1}\right\} \\ $$ | ||